There is a blind spot in AI research - Crawford, Kate; Calo, Ryan (Nature (London), 2016)
On 12 October, the White House published its report on the future of artificial intelligence (AI) - a product of four workshops held between May and July 2016 in Seattle, Pittsburgh, Washington DC and New York City (see go.nature.com/2dx8rv6).